Protective effect of the association of curcumin with piperine on prostatic lesions: New perspectives on BPA-induced carcinogenesis - Facina, Camila Helena [UNESP]; Campos, Silvana Gisele Pegorin [UNESP]; Ruiz, Thalles Fernando Rocha [UNESP]; Góes, Rejane Maira [UNESP]; Vilamaior, Patrícia Simone Leite [UNESP]; Taboga, Sebastião Roberto [UNESP] (Elsevier, 2021)
Bisphenol A (BPA) is a chemical agent which can exert detrimental effects on the male reproductive system, especially the prostate gland. In this study we described the efficacy of the dietary agent curcumin, alone or combined with piperine, to suppress the impact of BPA on the prostate. Adult gerbils were divided into nine experimental groups (n = 7 each group), regarding control (water and oil), exposed to BPA (50 μg/kg/day in water) or curcumin (100 mg/kg) and/or piperine (20 mg/kg). To evaluate the effects of the phytotherapic agents, the other groups received oral doses every two days, BPA plus curcumin (BCm), piperine (BP), and curcumin + piperine (BCmP). BPA promoted prostatic inflammation and morphological lesions in ventral and dorsolateral prostate lobes, associated with an increase in androgen receptor-positive cells and nuclear atypia, mainly in the ventral lobe. Curcumin and piperine helped to minimize these effects. BPA plus piperine or curcumin showed a reduction in nuclear atypical phenotype, indicating a beneficial effect of phytochemicals. Thus, these phytochemicals minimize the deleterious action of BPA in prostatic lobes, especially when administered in association. The protective action of curcumin and piperine consumption is associated with weight loss, anti-inflammatory potential, and control of prostate epithelial cell homeostasis.
Keywords: Endocrine disruptor; Inflammation; Obesity; Phytochemicals